THE ISOMERIZATION AND OXIDATION OF CAROTENOID COMPOUNDS IN THE OIL PALM FRUIT DURING PRODUCTIONS OF CPO - Reni Subawati Kusumaningtyas; Leenawaty Limantara (Indonesian Journal of Chemistry, 2009)
Isomerization and oxidation have been known as the major factors of the degradation of carotenoid compounds. Results showed that the isomerization of the carotenoid in the oil palm fruit, during the sterilization process, promotes the decrease of the concentration of trans a- and trans b-carotene approximately 21and 8%. The decrements have continued on the fruit digestion, pressing, and clarification processes. The isomerization is also indicated by the decreasing of the main peak spectra absorption intensity of a- and b-carotene about ±10,4%. The spectra  showed hypsocromic shift by ±3 nm. On the other hand, the oxidation of carotenoid has occurred in all steps of crude palm oil (CPO) production. The oxidation of a-carotene has caused the increasing amount of lutein: 49% of fruit after sterilization proces (BSt), 57% of crude oil after pressing (MSK), 17% of oil expurifier (MPF), and 5% of CPO product. The oxidation of b-carotene will increase the amount of zeaxantin: 53% of fruit after sterilization proces (BSt), 9% of crude oil after pressing (MSK), and 4% of oil expurifier (MPF).